Asymmetric synthesis of tertiary thiols and thioethers - Clayden, Jonathan; MacLellan, Paul (Beilstein Journal of Organic Chemistry, 2011)
Enantiomerically pure tertiary thiols provide a major synthetic challenge, and despite the importance of chiral sulfur-containing compounds in biological and medicinal chemistry, surprisingly few effective methods are suitable for the asymmetric synthesis of tertiary thiols. This review details the most practical of the methods available.
Keywords: asymmetric synthesis; organolithium; sulfur; substitution; thiol